From Galileo to Newton - Hall, A. Rupert (Dover Publications, 1981)
Contents: From Galileo to Newton describes those new patterns of thought that emerged during this time of great excitement and widespread controversy. It discusses the discoveries revealed by telescope and microscope in the work of Huygens and Leeuwenhoek, and the new speculations to which these gave rise; Boyle's attempts to include chemical experiments within a rational theory of matter, and those begun by Descartes to explain the workings of the body on the basis of chemical and physical principles; and the revolutionary ideas in astronomy that generated the transition from the Ptolemaic concept of the universe to the Copernican and the subsequent acceptance of the heliostatic system.